2020
DOI: 10.1101/2020.01.24.918649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a growing population of eastern migratory monarch butterflies is currently insufficient

Abstract: The eastern migratory population of monarch butterflies has experienced a multi-10 decadal decline, but a recent increase in abundance (to 6.05 ha in winter 2018) has led some 11 observers to question whether the population has reversed its long-standing decline and 12 embarked on a trajectory of increasing abundance. We examined this possibility through 13 changepoint analyses, first assessing whether a change in trajectory existed and whether that 14 change was sufficient to alter our estimated risk for the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 15 publications
(24 reference statements)
1
22
0
Order By: Relevance
“…The continued evaluation of these insecticides at these locations may refine these estimates as trajectories of change near the terminus of a time series may be difficult to determine. 36 Resistance to pesticides is an ever-increasing challenge to global agriculture with nearly a 1000 species of pests, including approximately 600 arthropod species, resistant to one or more pesticides. 20 Resistance to a pesticide can be directly documented by demonstrating a reduction in susceptibility over time within a population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The continued evaluation of these insecticides at these locations may refine these estimates as trajectories of change near the terminus of a time series may be difficult to determine. 36 Resistance to pesticides is an ever-increasing challenge to global agriculture with nearly a 1000 species of pests, including approximately 600 arthropod species, resistant to one or more pesticides. 20 Resistance to a pesticide can be directly documented by demonstrating a reduction in susceptibility over time within a population.…”
Section: Discussionmentioning
confidence: 99%
“…At UMORE, the estimated slope of percent control after the change point was approximately five times that of SWROC, although not statistically different because of the wide confidence intervals. The continued evaluation of these insecticides at these locations may refine these estimates as trajectories of change near the terminus of a time series may be difficult to determine 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public concern for the monarch escalated after declines were identified in the eastern population (Brower et al 2012). The population remains well below its previous maximum-observed size (Thogmartin et al 2020) and has recently been declared deserving of protection under the Endangered Species Act, although it was not listed so that other species could be prioritized for management (USFWS 2020). This means that continual monitoring and reassessment of the monarch will remain a critical need both to understand its dynamics but also to provide the US Fish and Wildlife Service the information they require for their yearly deliberations.…”
Section: The Monarch Butterfly As a Model System For Global Change Ecologymentioning
confidence: 99%
“…The eastern North American migratory monarch population has "undergone a precipitous decline over the last two decades" (Semmens et al, 2018), and recent indications of a population resurgence are not reliable (Thogmartin et al, 2020). Wilcox et al (2019) identified five broad threats to monarchs, with changing climate conditions and the loss of overwintering and breeding habitat likely the greatest (see also Saunders et al, 2018 andFlores-Martínez et al, 2019).…”
Section: Monarch Butterflies: Global North ↔ Global South and Urban ↔...mentioning
confidence: 99%